2021
DOI: 10.35965/jbm.v2i2.412
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Dukcapil Kabupaten Sinjai

Abstract: Penelitian ini bertujuan untuk menganalisis pengaruh gaya kepemimpinan, motivasi dan disiplin kerja terhadap kinerja pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sinjai. Dimana rumusan masalahnya adalah bagaimana pengauh gaya kepemimpinan, motivasi dan disiplin kerja terhadap kinerja pegawai pada dinas dukcapil Kabupaten Sinjai. Tujuannya untuk mengetahui hubungan dan pengaruh gay kepemimpinan motivasi dan disiplin kerja pada kinerja pegawai dias Dukcapil Kabupaten Sinjai. Metode dan teknik a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…The results of this study can be said to support the theoretical concept put forward by Notoatmodjo (2002), which says that discipline is an attitude and behavior that can be shown by every worker or employee in complying with the provisions and rules that have been set to achieve organizational goals. In addition, this study has also supported research results (Izzaty et al, 2022;Nurhanan et al, 2021;Yekti, 2012) which found that work discipline has a positive and significant effect on employee performance.…”
Section: ) the Effect Of Discipline On Apparatus Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study can be said to support the theoretical concept put forward by Notoatmodjo (2002), which says that discipline is an attitude and behavior that can be shown by every worker or employee in complying with the provisions and rules that have been set to achieve organizational goals. In addition, this study has also supported research results (Izzaty et al, 2022;Nurhanan et al, 2021;Yekti, 2012) which found that work discipline has a positive and significant effect on employee performance.…”
Section: ) the Effect Of Discipline On Apparatus Performancesupporting
confidence: 87%
“…Human resource management (HRM) is a field of general management which includes aspects of planning, organizing, implementing and controlling (Nurhanan et al, 2021). This process is contained in the functions/fields of production, marketing, finance, and staffing.…”
Section: Literature Review 1) Human Resource Managementmentioning
confidence: 99%
“…Manajemen Sumber Daya Manusia Manajemen sumber daya manusia (MSDM) merupakan salah satu bidang dari manajemen umum yang meliputi segi-segi perencanaan, pengorganisasian, pelaksanaan dan pengendalian (Nurhanan et al, 2021). Proses ini terdapat dalam fungsi/bidang produksi, pemasaran, keuangan, maupun kepegawaian.…”
Section: IIunclassified
“…Hasil penelitian ini dapat dikatakan mendukung konsep teori yang dikemukakan oleh Notoatmodjo (2002), yang mengatakan bahwa disiplin sebagai suatu sikap dan perilaku yang dapat ditunjukkan oleh setiap pekerja atau pegawai dalam mematuhi ketentuan dan aturan yang telah ditetapkan untuk mencapai tujuan organisasi. Di samping itu, penelitian ini juga telah mendukung hasil penelitian (Izzaty et al, 2022;Nurhanan et al, 2021;Yekti, 2012) yang menemukan bahwa kedisiplinan kerja berpengaruh positif dan signifikan terhadap kinerja pegawai.…”
Section: Pengaruh Disiplin Terhadap Kinerja Aparaturunclassified